The Barth–Bultmann Correspondence - Grau, H. Gerhard (Theology today, 1973)
The newly-published letters between Barth and Bultmann“give us new information about the intensity of their relationship. Of course, in this correspondence one does not find a brand-new theology. What is so fascinating about them is that theology is done here in a personal context. One observes how these two theologians as persons wrestle with the frontiers of faith and knowledge in the personal medium of letters.